Stalled!: Transforming Public Restrooms - Joel Sanders (Footprint)
Joel Sanders interrogates the intersections of architecture, public space, gender and sexuality with his project for public restrooms Stalled!. Stalled! involves an interdisciplinary design research project in which Sanders collaborates together with gender studies professor Susan Stryker, and law professor Terry Kogan. Stalled! proposes to regard access to public restrooms as a social justice issue with design consequences that can be solved with innovative architectural solutions. The project aims to create restrooms that not only meet the needs of the trans community, but encompass the needs of all embodied subjects of different ages, genders and abilities.